2018
DOI: 10.1002/ajmg.a.38596
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mosaic deletions involving SCN1A cause Dravet syndrome

Abstract: Somatic mosaicism in single nucleotide variants of SCN1A is known to occur in a subset of parents of children with Dravet syndrome (DS). Here, we report recurrent somatic mosaic microdeletions involving SCN1A in children diagnosed with DS. Through the evaluation of 237 affected individuals with DS who did not show SCN1A or PCHD19 mutations in prior sequencing analyzes, we identified two children with mosaic microdeletions covering the entire SCN1A region. The allele frequency of the mosaic deletions estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…4) in both likely pathogenic and benign variants, apart from two likely pathogenic variants in SCN1A and SCN8A that appeared to have significantly higher VAF in saliva than blood. SCN1A has previously been shown to harbour differential levels of mosaicism across different tissues 35 , and both genes are well-known sources of mosaic diagnoses in epilepsy 30,36,37 . The likelihood that a variant validated as mosaic in the proband was strongly correlated with both the WES variant allele fraction (VAF) and the strength of statistical evidence (binomial p -value) for a deviation of VAF away from 0.5 (Table 1 and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4) in both likely pathogenic and benign variants, apart from two likely pathogenic variants in SCN1A and SCN8A that appeared to have significantly higher VAF in saliva than blood. SCN1A has previously been shown to harbour differential levels of mosaicism across different tissues 35 , and both genes are well-known sources of mosaic diagnoses in epilepsy 30,36,37 . The likelihood that a variant validated as mosaic in the proband was strongly correlated with both the WES variant allele fraction (VAF) and the strength of statistical evidence (binomial p -value) for a deviation of VAF away from 0.5 (Table 1 and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We then investigated potential changes in amino acid signalling in epilepsy models. First, we employed a heterozygous Scn1a +/− mouse model lacking one copy of the Na V 1.1 protein (Thiele et al, 2018) that is used as a model for a variety of seizure types from simple febrile seizures to severe genetic disorders such as Dravet (Nakayama et al, 2018) and Lennox–Gastaut syndromes (Zhou et al, 2018). We initially analysed brain amino acid levels in healthy (wild‐type) and Scn1a +/− mice, where a significant increase in glycine ( P < .05) and methionine ( P < .05) levels and a decrease in cysteine ( P < .05) levels were found in these epileptic model mice compared to wild‐type controls (Figure 6a).…”
Section: Resultsmentioning
confidence: 99%
“…Increasing evidence suggested that mosaic mutations had counted for a certain fraction of monogenic disorders, well known in tumorigenesis and overgrowth syndromes (Erickson, 2014;Tate et al, 2019). Recently, case reports had shown mosaicism in certain epilepsy-related and neurodevelopmental genes (Nakayama et al, 2018;Liu et al, 2019;Zhang et al, 2019). Stosser et al (2018) firstly performed a systematic study of the extent and level of mosaicism detectable by NGS for patients with epilepsy (Stosser et al, 2018).…”
Section: Discussionmentioning
confidence: 99%